Rating the Effectiveness of Fishery Closures With Visible Infrared Imaging Radiometer Suite Boat Detection Data - Elvidge, Christopher D.; Ghosh, Tilottama; Baugh, Kimberly; Zhizhin, Mikhail; Hsu, Feng-Chi; Katada, Nilo Selim; Penalosa, Wilmon; Hung, Bui Quang (Frontiers in Marine Science, 2018)
Fishery closures are widely used to promote the sustainability of fish stocks. Fishery agencies typically have very little data relevant to planning closure enforcement actions and evaluating the effectiveness of closures, due in part to the vast expanse and remote nature of many closures. In some cases the effectiveness of closures can be evaluated using data from GPS based beacons, such as Automatic Identification System (AIS) or Vessel Monitoring Systems (VMS) installed on fishing boats. In fisheries where few boats are equipped with AIS or VMS, the rating of closures relies on other data sources capable of detecting or inferring fishing activity. One such source comes from low light imaging data collected by the NASA/NOAA Visible Infrared Imaging Radiometer Suite (VIIRS), which can detect fishing boats using lights to attract catch. This is a widely used practice in Asia and several other regions. NOAA has developed an automatic system for reporting the locations of VIIRS boat detections with a nominal four hour temporal latency. VIIRS boat detection alerts are running for more than 900 fishery closures in the Philippines, with email and SMS transmission modes. These alerts are being actively used in the Philippines to plan enforcement actions and there is a growing list of apprehensions that occurred based on tip-offs from VIIRS. The VIIRS boat detection archive extends back to April 2012. A VIIRS closure index (VCI) has been developed to rate the effectiveness of closures on monthly increments in terms of a percentage. The VCI analysis was performed on three types of closures: an ad hoc fishery closure associated with a toxic industrial discharge, a seasonal fishery closure and a permanent closure in restricted coastal waters. The VCI results indicate that it is possible to rank the effectiveness of different closure, year-to-year differences in compliance levels, and to identify closure encroachments which may warrant additional enforcement effort.